Respuesta :

I use the substitution method, but you can also use elimination and matrix

1. Solve for y in 3x+y=14
y=14-3x

2. Substitute y=14-3x into x+2y=3
-5x+28=3

3. Solve for x in -5x+28=3
x=5

4. Substitute x=5 into y=14-3x
y=-1

5. Therefore,
x=5
y=-1

Have a nice day :D
You can use a bunch of different methods here, but I'll use substitution.

For the second equation, you can bring the 2y to the right side to isolate the x:

x=-2y+3

You can then substitute this into the first equation to find out y:

3x+y=14
3(-2y+3)+y=14
-6y+9+y=14
-5y=5
y=-1

Now you can plug in y to the second equation to find x:

x=-2y+3
x=-2(-1)+3
x=2+3
x=5

Therefore:
x=5
y=-1